2019
DOI: 10.1371/journal.pone.0212852
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of artists in major U.S. museums

Abstract: The U.S. art museum sector is grappling with diversity. While previous work has investigated the demographic diversity of museum staffs and visitors, the diversity of artists in their collections has remained unreported. We conduct the first large-scale study of artist diversity in museums. By scraping the public online catalogs of 18 major U.S. museums, deploying a sample of 10,000 artist records comprising over 9,000 unique artists to crowdsourcing, and analyzing 45,000 responses, we infer artist genders, et… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…We provide details about the information requested later in this section, and we provide the full text of our Amazon Mechanical Turk questionnaire in S1 Appendix. A number of peer-reviewed published studies adopt this crowdsourcing methodology to infer demographics; see, for example, work on diversity in art and diversity on mathematical sciences journal editorial boards [11,12]. We adopted several strategies to ensure data quality.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We provide details about the information requested later in this section, and we provide the full text of our Amazon Mechanical Turk questionnaire in S1 Appendix. A number of peer-reviewed published studies adopt this crowdsourcing methodology to infer demographics; see, for example, work on diversity in art and diversity on mathematical sciences journal editorial boards [11,12]. We adopted several strategies to ensure data quality.…”
Section: Methodsmentioning
confidence: 99%
“…To omit them would make this research less verifiable. Third and last, the crowdsourcing approach to inferring demographics of public figures based on public information has been previously established in the literature [11,12]. We now describe in more detail the procedures we applied to each raw data record for each question on our survey instrument that is contained in our final data set.…”
Section: Demographic Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we know that the US art market is characterized by deep systemic issues of race (and gender) inequality. For instance, a recent study found that 85% of artists who have works exhibited in 18 US major museums are white and 87% are men (Topaz et al, 2019), and similar compositions go for art fairs and arts education. 4 Hence, there is scope to assume that the ethnic composition of the local art community in Bushwick is largely white.…”
Section: Bushwickmentioning
confidence: 99%
“… 8 , 9 Much of art-based education, however, is museum-based, where art is often not representative of the diversity of surrounding communities. 6 , 10 , 11 Conversely, murals are a form of social expression often designed by or in conjunction with community members. Directly embedded into built environments, they evolve as neighborhoods change.…”
Section: Introductionmentioning
confidence: 99%